2016
DOI: 10.1055/s-0042-119034
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with simethicone and N-acetylcysteine in improving visibility during upper endoscopy: a double-blind randomized trial

Abstract: Upper endoscopy is the most common method for the diagnosis of upper gastrointestinal tract diseases. The aim of this study was to determine whether premedication with simethicone or -acetylcysteine improves mucosal visualization during upper endoscopy. This was a randomized, double-blind, placebo-controlled study of 297 patients scheduled for upper endoscopy who were premedicated 15 - 30 minutes before the procedure with: 100 mL of water (placebo, group A); water plus 100 mg simethicone (group B); water plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 20 publications
2
57
0
7
Order By: Relevance
“…Moreover, most of the endoscopies performed in this study were without sedation or general anesthesia, thus limiting the tolerance of the procedure and the time spent to analyze the gastric mucosa. It has also been proven that the use of mucolytic agents (N-acetylcystein, simeticone) was efficient to improve the endoscopist's ability to detect lesions [33][34][35], but this procedure was routine practice at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the endoscopies performed in this study were without sedation or general anesthesia, thus limiting the tolerance of the procedure and the time spent to analyze the gastric mucosa. It has also been proven that the use of mucolytic agents (N-acetylcystein, simeticone) was efficient to improve the endoscopist's ability to detect lesions [33][34][35], but this procedure was routine practice at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both the drugs can improve the mucosal visibility of UGI endoscopy [ 6 , 10 , 11 ]. Previous studies on UGI endoscopy premedication have focused on mucosal visibility [ 4 , 7 , 9 , 12 15 ], and a recently published double-blind randomized trial has proved that both pronase and simethicone can result in better visibility [ 16 ]. However, the detection rate improvement on UGI early cancer and precancerous lesions through oral premedication has not been well evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that the addition of simethicone to the bowel preparation improved the visibility [12,15] and a systematic review concluded that supplemental use of oral simethicone before endoscopy improves the small bowel visibility, decreases air bubbles in the colonic lumen but does not affect the completion rate of colonoscopies [16]. There is also improved visibility with pre-medication using simethicone before esophagogastroduodenoscopy [17,18]. However, to the best of our knowledge, this is the first observation that indicates that a minor modification such as the elimination of simethicone from the auxiliary channel water pump solution results in a substantial reduction of the polyp detection rate.…”
Section: Discussionmentioning
confidence: 99%